Islamic New Year Celebration: Collaboration Between KKN Students and the Community in Torch Parade and Islamic Competitions in Jorong LumbaruPer: ingatan Tahun Baru Islam: Kolaborasi Mahasiswa KKN dan Masyarakat dalam Pawai Obor dan Lomba Islami di Jorong Lumbaru - Ika Parma Dewi; Chelsea Defista; Ilmi Okcya Pratami; Aulia Adrinovra; Nabila Marsyanada; Muhammad Hanif; Rahma Fadhilah; Putri Wahyuni (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
This community-based study highlights the collaboration between students of the Community Service Program (KKN) from Universitas Negeri Padang and the residents of Jorong Lumbaru in commemorating the Islamic New Year 1447 H. The program involved a torch parade and Islamic competitions, including adzan, tartil, and tilawah, with active participation from children, youth, and local leaders. Students were directly involved from planning to execution. Field observations and post-event interviews showed that this collaboration not only strengthened communal ties but also increased youth engagement in religious activities. The torch parade served as both a cultural expression and a platform for Islamic spiritual outreach, while the competitions contributed to building religious identity and character education among the younger generation. This activity illustrates the role of KKN in promoting social responsibility and empathy among students, while simultaneously preserving contextual Islamic traditions. Ultimately, this initiative serves as a strategic step toward fostering a harmonious, religiously-rooted community.